Effects of Freeze–Thaw Cycle with and without Proteolysis Inhibitors and Cryopreservant on the Biochemical and Biomechanical Properties of Articular Cartilage. (April 2014) - Qu, Chengjuan; Hirviniemi, Mikko; Tiitu, Virpi; Jurvelin, Jukka S.; Töyräs, Juha; Lammi, Mikko J.
Objective : We investigated the effects of freeze-thawing on the properties of articular cartilage. Design : The reproducibility of repeated biomechanical assay of the same osteochondral sample was first verified with 11 patellar plugs from 3 animals. Then, 4 osteochondral samples from 15 bovine patellae were divided into 4 groups. The reference samples were immersed in phosphate-buffered saline (PBS) containing proteolysis inhibitors and biomechanically tested before storage for further analyses. Samples of group 1 were biomechanically tested before and after freeze-thawing in PBS in the absence and those of group 2 in the presence of inhibitors. Samples of the group 3 were biomechanically tested in PBS-containing inhibitors, but frozen in 30% dimethyl sulfoxide/PBS and subsequently tested in PBS supplemented with the inhibitors. Glycosaminoglycan contents of the samples and immersion solutions were analyzed, and proteoglycan structures examined with SDS-agarose gel electrophoresis. Results : Freeze-thawing decreased slightly dynamic moduli in all 3 groups. The glycosaminoglycan contents and proteoglycan structures of the cartilage were similar in all experimental groups. Occasionally, the diffused proteoglycans were partly degraded in group 1. Digital densitometry revealed similar staining intensities for the glycosaminoglycans in all groups. Use of cryopreservant had no marked effect on the glycosaminoglycan loss during freeze-thawing. Conclusion : The freeze-thawed cartilage samples appear suitable for the biochemical and biomechanical studies.